HUBUNGAN ADVERSITY QUOTIENT DENGAN SCHOOL WELLBEING PADA SISWA SMP - Onik Wahyu Utami; Yulia Fitriani; Yuarini Wahyu Pertiwi (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the relationship between Adversity Quotient and School Wellbeing in junior high school students. Adversity Quotient describes an individual's ability to face, survive, and recover from difficulties, while School Wellbeing refers to student well-being, which includes feelings of safety, comfort, acceptance, and a sense of purpose in the school environment. The method used in this study is a quantitative approach with a random sampling technique, involving 151 respondents. The instruments used are the Adversity Quotient Scale and the School Wellbeing Scale, which have met the requirements for validity and reliability. Data analysis was carried out using the Spearman test because the data were not normally distributed. The results of the analysis showed a significant positive relationship between Adversity Quotient and School Wellbeing. This finding indicates that students who have a higher ability to face challenges tend to have a better level of well-being at school. This indicates the importance of developing borrowing power and self-resilience in supporting student well-being in the educational environment.